A galectin‐specific signature in the gut delineates Crohn's disease and ulcerative colitis from other human inflammatory intestinal disorders. (1st February 2016) - Papa Gobbi, Rodrigo; De Francesco, Nicolás; Bondar, Constanza; Muglia, Cecilia; Chirdo, Fernando; Rumbo, Martín; Rocca, Andrés; Toscano, Marta A.; Sambuelli, Alicia; Rabinovich, Gabriel A.; Docena, Guillermo H.
Abstract: Inflammatory bowel diseases (IBD) are chronic and relapsing inflammatory conditions of the gastrointestinal tract including Crohn's disease (CD) and ulcerative colitis (UC). Galectins, defined by shared consensus amino acid sequence and affinity for β‐galactosides, are critical modulators of the inflammatory response. However, the relevance of the galectin network in the pathogenesis of human IBD has not yet been explored. Here, we analyzed the expression of relevant members of the galectin family in intestinal biopsies, and identified their contribution as novel mucosal markers in IBD. Colonic biopsies were obtained from 59 IBD patients (22 CD and 37 UC), 9 patients with gut rejection after transplantation, 8 adult celiac patients, and 32 non‐IBD donors. Galectin mRNA expression was analyzed by RT‐PCR and qPCR using specific primers for individual galectins. A linear discriminant analysis (LDA) was used to analyze galectin expression in individual intestinal samples. Expression of common mucosal‐associated galectins (Gal‐1, −3, −4, −9) is dysregulated in inflamed tissues of IBD patients compared with non‐inflamed IBD or control samples. LDA discriminated between different inflammation grades in active IBD and showed that remission IBD samples were clusterized with control samples. Galectin profiling could not distinguish CD and UC. Furthermore, inflamed IBD was discriminated from inflamed tissue of rejected gut in transplanted patients and duodenum of celiac patients, which could not be distinguished from control duodenum samples. The integrative analysis of galectins discriminated IBD from other intestinal inflammatory conditions and could be used as potential mucosal biomarker. © 2016 BioFactors, 42(1):93–105, 2016